2022
DOI: 10.1021/acs.jchemed.1c01267
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Validation of an Assessment Method Using Molecular Models Following Stereochemistry Instruction in an Organic Chemistry Course

Abstract: This paper describes an innovative method to evaluate students’ learning after teaching the topic of stereochemistry using molecular models in an organic chemistry course for second-year pharmacy students at Princess Nourah bint Abdulrahman University. This method is practical and relevant and directly measures the intended learning skills. It is also easy to structure, standardized, and less time-consuming to grade. The students’ outcomes using this method are presented and compared to outcomes of a conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…When the assessment is carried out via a single method, as in BC, which mainly involved the application of a heteroevaluation based on rote contents, 26 students who are not very proficient for this type of evaluation are at a disadvantage, always obtaining the same negative results. 31 Coinciding with these results, recent studies 39 conclude that inequality in basic chemistry courses diminishes with the introduction of the diversification of assessment processes. Furthermore, according to Bortnik el al., 40 context-based exams, such as those implemented in BCHS, favor the development of Higher Order Cognitive Skills (HOCS), improving students' academic outcomes.…”
Section: Relationships Between the Course Characteristics And Academi...mentioning
confidence: 85%
“…When the assessment is carried out via a single method, as in BC, which mainly involved the application of a heteroevaluation based on rote contents, 26 students who are not very proficient for this type of evaluation are at a disadvantage, always obtaining the same negative results. 31 Coinciding with these results, recent studies 39 conclude that inequality in basic chemistry courses diminishes with the introduction of the diversification of assessment processes. Furthermore, according to Bortnik el al., 40 context-based exams, such as those implemented in BCHS, favor the development of Higher Order Cognitive Skills (HOCS), improving students' academic outcomes.…”
Section: Relationships Between the Course Characteristics And Academi...mentioning
confidence: 85%
“…As a result, learning it depends on students’ representational and spatial thinking abilities. In this regard, gamification of stereochemistry has been shown to increase student comprehension and engagement in this topic. ,,,,,,,, …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, gamification of stereochemistry has been shown to increase student comprehension and engagement in this topic. 5,14,16,17,19,37,44,45,55 The results of the activity assessment showed high levels of agreement on the benefits of the game; however, only 60% of the students found that the history cards bring added value to the game. In our opinion, it is important to get students interested in the history of chemistry discoveries and major advances as a cultural complement to scientific knowledge.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Therefore, this assignment can help medicinal chemistry instructors enrich their courses through diverse evaluation methods that can distinguish levels of cognition by students. 21 This rubric was a modified version of the unified college rubric forms established for written assignments. A specialized scientific committee at the college constructed the unified rubric forms based on the educational outcomes set by the CAPE (Center for the Advancement of Pharmacy Education) and the standards set by the ACPE (Accreditation Council for Pharmacy Education).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The assessment of this activity also allowed instructors to measure course learning outcomes via a rubric format that clearly outlined the assessment criteria. Therefore, this assignment can help medicinal chemistry instructors enrich their courses through diverse evaluation methods that can distinguish levels of cognition by students . This rubric was a modified version of the unified college rubric forms established for written assignments.…”
Section: Introductionmentioning
confidence: 99%